Handbook of semiconductor wafer cleaning technology : science, technology, and applications - Kern, Werner, 1925- (Materials science and process technology series. Electronic materials and process technology., 1993)
Discusses semiconductor wafer cleaning and the scientific and technical disciplines associated directly or indirectly with this subject. Intended to serve as a handbook for practitioners and professionals in the field.